PENGARUH PERTUMBUHAN PENJUALAN, LIKUIDITAS, LEVERAGE, DAN STRUKTUR MODAL TERHADAP PROFITABILITAS (StudiEmpirispada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2016) - EriImroatulAnisak, 14.05.52.0263; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2018)
This study examinesthe effect of sales growth, liquidity, leverage, and capital structure to profitability. This research was conducted at the Indonesia Stock Exchange by using a go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2014 to 2016. Relationship and (or) influence between variable is described by using multiple regression analysis. The results showed that the sales growth has a positive effect And significant to profitability (Return On Asset),so that the first hypothesis was approved. Liquidity (Current Ratio) has a positive effect And significant to profitability (Return On Asset), thus it makes the second hypothesis was approved. Leverage (Debt of Equity Ratio) has a negative and significant effect to profitability (Return On Asset), so that the third hypothesis was approved.capital structure (Long Term Debt to Equity Ratio) did not have an effect on profitability (Return On Asset), so that the hypothesis was denied. Keyword: Sales Growth, Liquidity, Leverage, Capital Structure, Profitability.